Interacting dark energy models within the context of the particle creation framework: A dynamical systems study - Aman Shukla; Ashutosh Singh; Raghavendra Chaubey (Results in Physics)
In this paper, we employ the dynamical system method to probe the cosmological evolution in a matter creation model admitting interacting dark energy behavior. The set of dynamical variables in this framework allows one to trace the cosmic evolution in comparison to the Λ cold dark matter (ΛCDM) model. The critical points in cosmological phase space are analyzed for their stability nature. The numerical integrations of the autonomous system are used to extract the evolution of cosmological quantities of the model, subjected to the initial condition compatible with observational data. The resulting cosmological behavior observed from the dynamical variables, cosmographic parameters and statefinder analysis illustrate the similarity as well as deviations from the ΛCDM model during different cosmic expansion phases. The autonomous systems are also used to study the classical stability of models under consideration. The interacting dark energy scenario in the matter creation mechanism leads to the universe evolution, which traces their journey from the decelerating phase (composed of radiation and matter phase) into accelerating phase dominated by a negative pressure component, which is directly consistent with observations.